Generation, characterization and preclinical studies of a human anti-L1CAM monoclonal antibody that cross-reacts with rodent L1CAM. Issue 2 (17th February 2016) - Cho, Seulki; Park, Insoo; Kim, Haejung; Jeong, Mun Sik; Lim, Mooney; Lee, Eung Suk; Kim, Jin Hong; Kim, Semi; Hong, Hyo Jeong
ABSTRACT: L1 cell adhesion molecule (L1CAM) is aberrantly expressed in malignant tumors and plays important roles in tumor progression. Thus, L1CAM could serve as a therapeutic target and anti-L1CAM antibodies may have potential as anticancer agents. However, L1CAM is expressed in neural cells and the druggability of anti-L1AM antibody must be validated at the earliest stages of preclinical study. Here, we generated a human monoclonal antibody that is cross-reactive with mouse L1CAM and evaluated its pharmacokinetic properties and anti-tumor efficacy in rodent models. First, we selected an antibody (Ab4) that binds human and mouse L1CAM from the human naïve Fab library using phage display, then increased its affinity 45-fold through mutation of 3 residues in the complementarity-determining regions (CDRs) to generate Ab4M. Next, the affinity of Ab4M was increased 1.8-fold by yeast display of single-chain variable fragment containing randomly mutated light chain CDR3 to generate Ab417. The affinities (KD ) of Ab417 for human and mouse L1CAM were 0.24 nM and 79.16 pM, respectively. Ab417 specifically bound the Ig5 domain of L1CAM and did not exhibit off-target activity, but bound to the peripheral nerves embedded in normal human tissues as expected in immunohistochemical analysis. In a pharmacokinetics study, the mean half-life of Ab417 was 114.49 h when a single dose (10 mg/kg) was intravenously injected into SD rats. Ab417 significantly inhibited tumor growth in a human cholangiocarcinoma xenograft nude mouse model and did not induce any adverse effect in in vivo studies. Thus, Ab417 may have potential as an anticancer agent.